(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
This paper analyzed Income Tax to determine how Social Manufacturing Enterprises should proceed (SME) regarding taxes. The organization under study is Aluminio del Tuy C.A. (Alentuy), a national company that arises as a result of import substitution policy developed by the National Executive in the 70s. By June 15, 2010, according to Decree No. 7,463, a compulsory acquisition (expropriation) of personal property, and real estate was ordered so it became a state enterprise under control of the Ministry of Power Industry. Under this scenario, Alentuy becomes an SME, but framed under the Commercial Cod, it started operations as a Limited Company. Therefore, a situation emerges before IT act, where the term Social Manufacturing Enterprises (SME) is not considered in the current legislation. The study was based methodologically under a descriptive study and field. A questionnaire was used as data collection technique. The results indicated that the company requires the design of Tax General Guidelines, to achieve its objectives for achieving compliance with tax obligations